Innervation of the Nose and Nasal Region of the Rat: Implications for Initiating the Mammalian Diving Response - McCulloch, Paul F.; Lahrman, Kenneth A.; DelPrete, Benjamin; DiNovo, Karyn M. (Frontiers in Neuroanatomy, 2018)
Most terrestrial animals demonstrate an autonomic reflex that facilitates survival during prolonged submersion under water. This diving response is characterized by bradycardia, apnea, and selective increases in peripheral vascular resistance. Stimulation of the nose and nasal passages is thought to be primarily responsible for providing the sensory afferent signals initiating this protective reflex. Consequently the primary objective of this research was to determine the central terminal projections of nerves innervating the external nose, nasal vestibule, and nasal passages of rats. We injected Wheat Germ Agglutinin (WGA) into specific external nasal locations, into the internal nasal passages, and directly into trigeminal nerves innervating the nose and nasal region. The immunohistological pattern of WGA labeling from the nasal passages, from rats with and without intact anterior ethmoidal nerves (AENs), were compared to WGA labeling patterns from specific trigeminal nerves. After injecting WGA into the nasal passages, central projections were found prominently within the ventral tip of the medullary dorsal horn (MDH), between pyramidal decussation and obex, especially along the transition with spinal trigeminal nucleus interpolaris. This pattern of labeling was very similar to when WGA was directly injected into either the AEN or nasopalatine nerve. WGA labeling from the infraorbital nerve (ION) showed partial overlap with WGA labeling from the nasal passages, while more peripheral branches of the ION did not. Thus both the internal nasal branch of the ophthalmic AEN and the maxillary nasopalatine nerve are primarily responsible for innervating the nasal passages. We conclude that innervation of the anterior nasal passages by the AEN and nasopalatine nerve is likely to provide the afferent information responsible for the activation of secondary neurons within MDH during voluntary diving in rats